2017
DOI: 10.3390/fermentation3030031
|View full text |Cite
|
Sign up to set email alerts
|

Phenols Removal from Hemicelluloses Pre-Hydrolysate by Laccase to Improve Butanol Production

Abstract: Phenolic compounds are important inhibitors of the microorganisms used in the Acetone-Butanol-Ethanol (ABE) fermentation. The degradation of phenolic compounds in a wood pre-hydrolysate, a potential substrate for the production of ABE, was studied in this article. First, physicochemical methods for detoxification such as nanofiltration and flocculation were applied and the best combination was selected. With a flocculated sample, the concentration of phenolic compounds decreases from 1.20 to 0.28 g/L with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The laccase from T. versicolor was reported to detoxify furanic and phenolic aldehyde derivatives, and in the presence of a redox mediator, this enzyme broadened its activity to phenolic ketone derivatives (Saravanakumar et al 2016). The butanol production by Clostridium acetobutylicum was 2.7-fold higher than the untreated wood hydrolysate (Allard-Massicotte et al 2017). According to the previous study, a combination of hydrolysate flocculation and laccase treatment reduced phenolic concentration from 1.20 to 0.28 g/L.…”
Section: Laccases (Aa1)mentioning
confidence: 79%
“…The laccase from T. versicolor was reported to detoxify furanic and phenolic aldehyde derivatives, and in the presence of a redox mediator, this enzyme broadened its activity to phenolic ketone derivatives (Saravanakumar et al 2016). The butanol production by Clostridium acetobutylicum was 2.7-fold higher than the untreated wood hydrolysate (Allard-Massicotte et al 2017). According to the previous study, a combination of hydrolysate flocculation and laccase treatment reduced phenolic concentration from 1.20 to 0.28 g/L.…”
Section: Laccases (Aa1)mentioning
confidence: 79%
“…Instead, they found total inhibition of bioethanol production when working with a vanillin concentration of 4000 mg/L. In addition, Allard-Massicotte et al [ 91 ], in their study about phenols removal from pre-hydrolysate by laccase, reported that a phenolic compounds concentration of 280 mg/L was far below the limit of inhibition in the acetone-butanol-ethanol fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…In butanol production, the acetone‐ n ‐butanol‐ethanol fermentation process, phenolic compounds inhibit microorganisms such as Clostridium sp. A study by Allard‐Massicotte et al 75 used laccase, nanofiltration, and flocculation to reduce phenolic content from 1.20 to 0.28 g/L in wood prehydrolysate, allowing 4.17 g/L butanol production. In another study, Yuejiao et al 76 used the bacterial strain Kurthia huakuii to detoxify pretreated corn stover from phenolics with laccases produced by this strain and used this material to produce lactic acid with Bacillus coagulans in an SSF process, achieving titers up to 33.5 g/L compared to 18 g/L without the detoxification step.…”
Section: Applications Of Laccases In the Production Of Biofuels And B...mentioning
confidence: 99%